Validation of ENVISAT (SCIAMACHY) versus Dobson and TOMS atmospheric ozone measurements in Athens, Greece: input for the upcoming IPY campaign - Varotsos, C. A.; Cracknell, Arthur Phillips (Taylor and Francis, 2007)
The intercomparison of the daily column ozone observations obtained by the SCanning Imaging Absorption SpectroMeter for Atmospheric CHartographY (SCIAMACHY), the Total Ozone Mapping Spectrometer (TOMS), and Dobson spectrophotometer over Athens, Greece, during 2002-2006 is attempted here. The results presented will be employed for the validation of the SCIAMACHY instrument, which is flown on the European Space Agency's Environmental satellite (ENVISAT) and provides its daily column ozone observations to the International Polar Year 2007-2008 activity, since 1 March 2007